Hyponatremia in a Teenager: A Rare Diagnosis. Issue 12 (December 2015) - Correia, Filipa; Fernandes, Alexandre; Mota, Teresa C.; Garcia, Milagros; Castro-Correia, Cíntia; Fontoura, Manuel; Ribeiro, Augusto
Abstract : Introduction: Hyponatremia is a common electrolyte alteration which has the potential for significant morbidity and mortality. Endocrine disorders, such as primary hypothyroidism and adrenal insufficiency are uncommon causes of hyponatremia. We present the case of a teenager with symptomatic hyponatremia caused by a rare disorder. Case: A 17-year-old boy was admitted to the emergency department with abdominal pain, nausea and vomiting, asthenia, and weight loss. He was in poor general condition, hypotensive, and he had dry mucous membranes and skin as well as mucosa hyperpigmentation. The laboratory findings showed severe hyponatremia, hyperkalemia, and renal dysfunction. The patient started inotropic support and antibiotics. Plasma cortisol and corticotropin levels allowed the diagnosis of primary adrenal insufficiency. He began replacement therapy with hydrocortisone and fludrocortisone, with gradual symptom resolution. An abdominal computed tomography scan showed adrenal hypoplasia. Findings for antiadrenal and antithyroid antibodies were positive, allowing the diagnosis of autoimmune polyglandular syndrome type II. Discussion: Adrenal insufficiency is a rare disease, especially in children, and its clinical manifestations are due to glucocorticoid and mineralocorticoid deficiency. In most of the cases, symptoms are nonspecific, requiring a high index of clinical suspicion. If the diagnosis and treatment are delayed, acute adrenal insufficiency carries a high morbidity and mortality.